Sosialisasi Perpajakan atas Transaksi E-Commerce pada Usaha Mikro, Kecil dan Menengah di Kecamatan Pademangan Jakarta Utara - Ayu Silviani Dewi; Bambang Irawan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
E-commerce transactions in Micro, Small and Medium Enterprises (MSMEs) need to be understood by MSME taxpayers as the largest number of business entities in Indonesia in fulfilling their tax obligations. The purpose of this study is to analyze the socialization of taxation on e-commerce transactions to MSMEs in Pademangan District, North Jakarta. The research approach used is qualitative with a qualitative descriptive method. The results of the study found that Publication, Counseling and Personal Approaches were appropriate methods or means of tax socialization in achieving the target of tax revenue and taxpayer compliance. By increasing the intensity of publications, counseling and personal approaches to these taxpayers, it is hoped that the target of tax revenue for e-commerce transactions can be achieved.